RUSSIAN-TAJIK RELATIONS: RESENT STATE AND FUTURE DEVELOPMENT - MULLOJANOV, Parviz (CENTRAL ASIA AND THE CAUCASUS, 2007)
Tajikistan is traditionally considered one of Russia’s most devoted and stable geopolitical allies in the post-Soviet space. Nevertheless, there have been both warming up and cooling off periods in the history of Russian Tajik relations, and they are fraught with a number of stumbling blocks, ulterior motives, and rather acute contradictions. So, a closer look reveals that the future of Russian-Tajik relations is not as surefire and problem-free as it may appear, at least, in the long term. The main thing to be figured out is what are the predominating problems and trends today in the development of the relations between the two countries and how will they affect the future? Will Tajikistan remain an outpost of Russian foreign policy in the Central Asian region, or will it gradually distance itself from Russia, turning into an independent geopolitical player or satellite for other regional and world powers? In 1991, after the Soviet Union collapsed and the former Soviet republics paraded their sovereignty, for some time, the Russian government regarded the events going on in Tajikistan as a struggle with the remnants of the communist past. Democrats, people from the Democratic Russia movement who had made their careers during the struggle with Gorbachev and suppression of the August coup of 1991, still predominated in President Yeltsin’s close circle at that time. The Russian democrats in power openly lobbied the interests of the Tajik opposition, with the leaders of which they enjoyed close relations since as early as perestroika times. In so doing, most of them genuinely believed that new Russia’s future lay in eradicating the old communist elites and establishing democratic conditions throughout the post-Soviet expanse. The group of so-called great power nationalists represented by professional government officials and employees of the national security and defense ministries were against this formulation of Russia’s foreign policy in the post-Soviet space. As a result, Russia’s policy toward Tajikistan was essentially paralyzed for several months, when the political leadership (at least a significant part of it) lobbied the interests of the Tajik opposition, and the national security and defense employees, particularly at the local level (in the form of border guards and the 201st motorized rifle division), openly supported the pro-government People’s Front.